Sistem Informasi Retribusi Terminal Berbasis Website - Suharsono Bantun; Jayanti Yusmah Sari; La Ode Hasnuddin S. Sagala; Hardianti Hardianti; Selviani Selviani (Faculty of Computer Science, University of Jember, 2022)
Retribution information system is very important and indispensable in a terminal. At the Sabilambo Kolaka Terminal, especially in recapitulating retribution income data, they still use recording in the ledger, this makes it difficult for terminal officers to make a report so that the process for reporting terminal retribution income data to the Transportation Office in its implementation is still not optimal and over time there are losses and losses. data collection in the form of sheets of paper. Based on these problems, the researchers conducted a study with the title